2021
DOI: 10.3390/pathogens10091152
|View full text |Cite
|
Sign up to set email alerts
|

Parasites Circulating in Wild Synanthropic Capybaras (Hydrochoerus hydrochaeris): A One Health Approach

Abstract: Capybaras (Hydrochoerus hydrochaeris) are affected by a wide range of protozoan and metazoan-derived parasitic diseases. Among parasites of free-ranging capybaras are soil-, water-, food- and gastropod-borne parasitosis, today considered as opportunistic infections in semiaquatic ecosystems. The overlapping of the capybara’s natural ecological habitats with human and domestic animal activities has unfortunately increased in recent decades, thereby enhancing possible cross- or spillover events of zoonotic paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Although this study did not detect parasite species of zoonotic or veterinary importance, it remains crucial to gain fundamental understanding of the composition and dynamics of parasite communities for monitoring wildlife species in natural areas adjacent to anthropic regions, particularly synanthropic species like the capybara. Notably, the capybara can be used as an effective indicator of ecosystem health, making the continuous monitoring of their populations a matter of public health concern (Uribe et al 2021). This study represents an initial exploration of the health status and parasite composition of capybaras from LPLIR, employing a non-invasive sampling methodology to detect a wide range of parasites without disturbing the wildlife populations residing in natural reserves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this study did not detect parasite species of zoonotic or veterinary importance, it remains crucial to gain fundamental understanding of the composition and dynamics of parasite communities for monitoring wildlife species in natural areas adjacent to anthropic regions, particularly synanthropic species like the capybara. Notably, the capybara can be used as an effective indicator of ecosystem health, making the continuous monitoring of their populations a matter of public health concern (Uribe et al 2021). This study represents an initial exploration of the health status and parasite composition of capybaras from LPLIR, employing a non-invasive sampling methodology to detect a wide range of parasites without disturbing the wildlife populations residing in natural reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife parasites are extremely important because they can modulate the dynamics of natural populations, and some of them are shared with domestic species, which can have economic consequences in production. Furthermore, wildlife acts as a reservoir for most of human zoonotic diseases (Uribe et al 2021). The interactions between parasites and their hosts can be altered by habitat disturbance through anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have identified six species of cestodes in the capybara with a higher prevalence than those reported in the lappe and agouti (see Table 1). Cestodes frequently reported included: Monoecocestus hagmanni Beddard, 1914, Monoecocestus hydrochoerus, Monoecocestus spp., Monoecocestus jacobi, Monoecocestus macrobursatum and Anoplocephalidae (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). It should be noted that in most cases cestodes found in the gastrointestinal tract did not result in clinical signs of diseases (9), however, Salas and Herrera (25) noted that there was a negative association between capybara infected with H. macrobursatum and their body condition.…”
Section: Gastrointestinal Cestodesmentioning
confidence: 99%